2016
DOI: 10.1007/s10826-016-0384-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Future Expectations of Low-Income Minority Young Men: Survival-Threats and Positive Expectations

Abstract: Future expectations, a subset of overall orientation, represent youths’ most realistic appraisals of future outcomes, and has been demonstrated to be associated with a range of health risk behaviors and wellbeing. The current study extends previous measurement efforts to operationalize and measure future expectations by estimating a multidimensional model of future expectations encompassing both positive and survival-based expectations, and using longitudinal data to test the consistency of these constructs ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Subsequent waves were collected when participants were, on average 13, 14, 15, 18 and 19 years of age (Prince et al, in press). Specifically, these youth included 208 African American and 133 Latino males residing in urban neighborhoods characterized by high violence and high poverty.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent waves were collected when participants were, on average 13, 14, 15, 18 and 19 years of age (Prince et al, in press). Specifically, these youth included 208 African American and 133 Latino males residing in urban neighborhoods characterized by high violence and high poverty.…”
Section: Methodsmentioning
confidence: 99%
“…During the first wave of interviews, there were a total of 341 fifth and seventh grade males (range ϭ 11-14 years, mean age ϭ 12.41 years). Subsequent waves were collected when participants were, on average 13, 14, 15, 18, and 19 years of age (Prince et al, 2016). Specifically, these youth included 208 African American and 133 Latino males residing in urban neighborhoods characterized by high violence and high poverty.…”
Section: Methods Original Databasementioning
confidence: 99%
“…As a result, this population may be more likely to experience hopelessness and less likely to envision a positive future for themselves (Logan, 2001; So, Gaylord-Harden, Voisin, & Scott, 2015; Stoddard et al, 2011). This hypothesis is supported by researchers who have found lower educational and occupational aspirations and more negative future expectations among low-income minority individuals living in urban centers compared to other populations (Duke, Skay, Pettingell, & Borowsky, 2009; Prince et al, 2016; Strayhorn, 2009).…”
Section: Exposure To Violence and Future Orientationmentioning
confidence: 86%
“…To our knowledge, the ML chi-square difference test, D ML , has only been evaluated in a large scale simulation study once (Chuang et al, 2015), where it was found to perform poorly in most conditions with nonnormal data, as would be expected. Prior to the current study it has never been evaluated with nonnormal multiple-group data, despite its frequent use in this context to assess measurement invariance (e.g., Clark et al, 2016; Gunnell, Bélanger, & Brunet, 2016; Huizink et al, 2016; Padilla-Walker & Jensen, 2016; Prince et al, 2016; Rice, Suh, Yang, Choe, & Davis, 2016; Veirman, Fontaine, & Van Ryckeghem, 2016). Consistent with expectations, we found that the ML chi-square difference test frequently exhibits inflated Type I error rates when data are not normally distributed.…”
Section: Discussionmentioning
confidence: 99%